ESTRO ACROP guidelines for target volume definition in the treatment of locally advanced non-small cell lung cancer. Issue 1 (April 2018) - Nestle, Ursula; De Ruysscher, Dirk; Ricardi, Umberto; Geets, Xavier; Belderbos, Jose; Pöttgen, Christoph; Dziadiuszko, Rafal; Peeters, Stephanie; Lievens, Yolande; Hurkmans, Coen; Slotman, Ben; Ramella, Sara; et al.
Abstract: Radiotherapy (RT) plays a major role in the curative treatment of locally advanced non-small cell lung cancer (NSCLC). Therefore, the ACROP committee was asked by the ESTRO to provide recommendations on target volume delineation for standard clinical scenarios in definitive (chemo)radiotherapy (RT) and adjuvant RT for locally advanced NSCLC. The guidelines given here are a result of the evaluation of a structured questionnaire followed by a consensus discussion, voting and writing procedure within the committee. Hence, we provide advice for methods and time-points of diagnostics and imaging before the start of treatment planning and for the mandatory and optional imaging to be used for planning itself. Concerning target volumes, recommendations are given for GTV delineation of primary tumour and lymph nodes followed by issues related to the delineation of CTVs for definitive and adjuvant radiotherapy. In the context of PTV delineation, recommendations about the management of geometric uncertainties and target motion are given. We further provide our opinions on normal tissue delineation and organisational and responsibility questions in the process of target volume delineation. This guideline intends to contribute to the standardisation and optimisation of the process of RT treatment planning for clinical practice and prospective studies.